Synthesis of nanostructured and biofunctionalized water-in-oil droplets as tools for homing T cells - Platzman, Ilia; Janiesch, Jan-Willi; Spatz, Joachim P. (Journal of the American Chemical Society, 2013)
Activation, ex vivo expansion of T cells, differentiation into a regulatory subset, and its phenotype-specific high-throughput selection represent major challenges in immunobiology. In part, this is due to the lack of technical means to synthesize suitable 3D extracellular systems to imitate ex vivo the cellular interactions between T cells and antigen-presenting cells (APCs). In this study, we synthesized a new type of gold-linked surfactant and used a drop-based microfluidic device to develop and characterize novel nanostructured and specifically biofunctionalized droplets of water-in-oil emulsions as 3D APC analogues. Combining flexible biofunctionalization with the pliable physical properties of the nanostructured droplets provided this system with superior properties in comparison with previously reported synthetic APC analogues.
Gesehen am 02.12.2021